Desvelando a vivência da implementação do processo de enfermagem em instituição hospitalar - Souza Junior, Deusdete Inacio De (2016)
The interest of this study is to analyze the implementation experience of the Nursing Process (NP) in a Hospital Institution. The development of NP enables effective compliance with ethical and professional determination in promoting assistance to the human being as a whole, ensuring that nursing interventions are designed to the individual and not to the disease. Corroborating the relevance of NP, some legal mechanisms were promulgated in Brazil, however, incorporate the NP to the practice and teaching of nursing, is still a great challenge for nurses; that live with difficulties to make it reality. In this context, emerged the research question that triggered the preparation of this study; - What strategies, difficulties and changes that permeate the implementation of NP in attendance? This study aimed to analyze the implementation experience of NP in a midrange and high complexity Private Hospital Institution, in a city in the south of Minas Gerais, Brazil. The theoretical foudation was achieved by an Integrative Literature Review Whittemore e Knalf (2005), which allowed the identification of deadlocks, conditions and capabilities to implement the NP. The Qualitative Approach was achieved with the Document Bardin ( 2013) and the Content Analysis (BARDIN, 2013). We used the technique of Focus Group (MINAYO, 2014) for data collection and the Thematic Analysis for data review (BARDIN, 2014) based on Symbolic Interaction (CHARON, 2010). From the documentary survey, 50 different documents were examined and identified the relevant events related to the implementation of the NP. Yet, the focus group was conducted with nurses in the study Hospital. Thematic analysis revealed meanings attributed by nurses and part listed agenda showed the nurse's interaction experience with the dynamics of implementation of NP in the hospital environment, with the centrality of the "Getting intentionality." Other major meanings are the following; Enabling the Nursing Process deployment with involving very involved and involving the institution; Making clinical evaluation, conducting and documenting the treatment plan and the Systematization of perioperative nursing care; Corroborating the recognition and establishment of identity, scientific and professional satisfaction and lastly, Overcoming impasses. This study may contribute to the stimulation and training of nurses for a possible NP implementation process in their practice, raising its therapeutic potential in the performance of clinical role. It also can be shared by nurses who yearn to work with the NP and sometimes not envision ways or starting points.